Highly redundant function of multiple AT-rich sequences as core promoter elements in the TATA-less RPS5 promoter of Saccharomyces cerevisiae - Sugihara, Fuminori (Oxford University Press, 2011)
In eukaryotes, protein-coding genes are transcribed by RNA polymerase II (pol II) together with general transcription factors (GTFs). TFIID, the largest GTF composed of TATA element-binding protein (TBP) and 14 TBP-associated factors (TAFs), plays a critical role in transcription from TATA-less promoters. In metazoans, several core promoter elements other than the TATA element are thought to be recognition sites for TFIID. However, it is unclear whether functionally homologous elements also exist in TATA-less promoters in Saccharomyces cerevisiae. Here, we identify the cis-elements required to support normal levels of transcription and accurate initiation from sites within the TATA-less and TFIID-dependent RPS5 core promoter. Systematic mutational analyses show that multiple AT-rich sequences are required for these activities and appear to function as recognition sites for TFIID. A single copy of these sequences can support accurate initiation from the endogenous promoter, indicating that they carry highly redundant functions. These results show a novel architecture of yeast TATA-less promoters and support a model in which pol II scans DNA downstream from a recruited site, while searching for appropriate initiation site(s).